Analisis Kemampuan Taruna Akademi Maritim Nusantara Dalam Memahami Konsep Fisika Mekanika - Andi Hermawan; Hari Sucahyowati (Universitas Pancasakti Tegal, 2019)
The ability to understand the physical concepts of mechanics in Applied Physics subjects is important for cadets. This understanding will later beused in the clarification of technical problems and ship engineering. The objectives of this study are (1) To produce a profile of the ability of theMaritime Academy cadets in understanding the concepts of mechanical physics, and (2) To show differences in physical abilities based on schoolorigin and regional origin. The subject of this research is the Nusantara Maritime academy cadets who have studied applied physics, and are in thesame semester. This type of research is observational with a cross-sectional approach. The main data collection of this study was obtained usingInterview techniques. In addition, there are supporting data which are the results of written research subjects' work in understanding physics physicsquestions. The results of this study are as follows: there is no difference in the ability of cadets to complete physics mechanics based on regional originwith a P value = 0.09 and there is a difference in the ability of cadets to complete mechanical physics based on educational origin with P = 0.043.